Folic acid in cleft lip, alveolus and palate prevention: Awareness among dental professionals - Elavenil P; Murugavel C; Kannadasan Kamal; Krishnakumar Raja V; Gnanam A; Kanimozhi G; Davis D (Wolters Kluwer Medknow Publications, 2010)
Objectives : To determine the awareness amongst dental students, practitioners and maxillofacial surgeons the role of folic acid in the prevention of CLAP and its clinical use. Materials and Methods : Questionnaire based study involving a sample base of 1100, comprising of dental students, practitioners and specialist maxillofacial surgeons. Results : hundred percent of the sample population were aware of CLAP disorders, of which 9.5 % believed that CLAP could be prevented. 3.8 % of the population were able to correlate folic acid to CLAP while a negligible 0.03 % could provide the dosage. Conclusion : Educating healthcare providers and, in turn, the prospective parents on benefits folic acid would not only help in reducing the incidence of CLAP but also significantly influence the economics of the patients afflicted with CLAP disorders.